Schools as opportunity for oral health promotion: Existing status in India - Chahar, Puneet; Jain, Meena; Sharma, Ankur; Yadav, Nisha; Mutneja, Parul; Jain, Vishal (Indian Journal of Child Health, 2018)
Childhood is a significant stage in people’s lives where they are more receptive toward behavior shaping; thus, schools have been considered important foundation in addressing the health and social issues. School oral health education programs have produced affirmative results in improving the overall health of the child. The aim of the current review was to explore the history of school health, models of school health and existing efforts of School Oral Health Programs (SOHP) in India. The review identified five existing SOHP (Indian Dental Association - Colgate’s “Young India” Bright Smiles, Bright Futures, Chacha Nehru Sehat Yojna - School health scheme [Government of Delhi], Neev - SOHP, Intensive Dental Health Care Program - Punjab, Trinity Care Foundation - Bengaluru, National Oral Health Program, AIIMS) which is either running or proposed. It is recommended that the upcoming SOHP should be crafted on the existing evidence-based guidelines and theoretical models of school health. Prompt execution of proposed programs should be the priority to target the optimum oral health of the children.